2016
DOI: 10.1016/j.cognition.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The not face: A grammaticalization of facial expressions of emotion

Abstract: Facial expressions of emotion are thought to have evolved from the development of facial muscles used in sensory regulation and later adapted to express moral judgment. Negative moral judgment includes the expressions of anger, disgust and contempt. Here, we study the hypothesis that these facial expressions of negative moral judgment have further evolved into a facial expression of negation regularly used as a grammatical marker in human language. Specifically, we show that people from different cultures expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 41 publications
3
47
2
Order By: Relevance
“…For example, it has been noted that, as in the case of emotional facial expressions, vocalizations produce concomitant facial movements around the mouth and other features, which could be processed simultaneously with auditory components (Ghazanfar & Takahashi, 2014). Psychological studies revealed that facial expressions are used as grammatical markers in face-to-face communication (Pfau & Quer, 2010;Benitez-Quiroz et al, 2016). Language studies also indicated that both mouth movements and the acoustic envelope of speech mainly exhibit a theta rhythm (2-7 Hz), which corresponds to the typical rhythm of dynamic facial expressions (Chandrasekaran et al, 2009).…”
Section: Lateralitymentioning
confidence: 99%
“…For example, it has been noted that, as in the case of emotional facial expressions, vocalizations produce concomitant facial movements around the mouth and other features, which could be processed simultaneously with auditory components (Ghazanfar & Takahashi, 2014). Psychological studies revealed that facial expressions are used as grammatical markers in face-to-face communication (Pfau & Quer, 2010;Benitez-Quiroz et al, 2016). Language studies also indicated that both mouth movements and the acoustic envelope of speech mainly exhibit a theta rhythm (2-7 Hz), which corresponds to the typical rhythm of dynamic facial expressions (Chandrasekaran et al, 2009).…”
Section: Lateralitymentioning
confidence: 99%
“…Campbell et al, 1999 ; Keltner et al, 2003 ; McCullough et al, 2005 ), which we will refer to as “expressives.” Several affective facial expressions associated with a set of basic emotional states such as anger, sadness, or joy are claimed to be universal and therefore cross-culturally conveyed in a similar way (cf. Ekman and Friesen, 1971 ; Izard, 1994 ; Benitez-Quiroz et al, 2016 ). Affective facial expressions include several types, however.…”
Section: Introductionmentioning
confidence: 99%
“…(See Benitez‐Quiroz et al. for a possible model, which seeks the evolutionary roots of the headshake used to express negation in sign and in gestures. )…”
Section: Animal Languagesmentioning
confidence: 99%